SOI based nanowire single-electron transistors: design, simulation and process development - Hashim, Uda (IJNeaM, Universiti Malaysia Perlis (UniMAP), 2007)
One of the great problems in current large-scale integrated circuits is increasing power dissipation in a small silicon chip. Single-electron transistor which operate by means of one-by-one electron transfer, is relatively small and consume very low power and suitable for achieving higher levels of integration. In this research, the four masks step are involved namely source and drain mask, Polysilicon gate mask, contact mask, and metal mask. The masks were designed using ELPHY Quantum GDS II Editor with a nanowire length and nanowire width of approximately 0.10Âµm and 0.010 Âµm respectively. In addition, the process flow development of SET and the process and device simulation of SET are also explained in this paper. The Synopsys TCAD simulation tools are utilized for process and device simulation. The results from the device simulation showed that the final SET was operating at room temperature (300K) with a capacitance estimated around 0.4297 aF.